2005
DOI: 10.1002/hep.20760
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of hepatitis B e antigen-negative chronic hepatitis B on long-term nucleos(t)ide analog therapy starting with lamivudine

Abstract: We determined the clinical outcome of hepatitis e antigen (HBeAg)-negative chronic hepatitis B patients treated with long-term nucleos(t)ide analog therapy starting with lamivudine. We evaluated 201 such patients treated for 3.8 ؎ 1.4 years and 2 historical similar cohorts: 1 treated with interferon-alfa (n ‫؍‬ 209) and 1 untreated (n ‫؍‬ 195). Virological or biochemical remission rate at 48 months under lamivudine was 34% or 36%, respectively, whereas adefovir was administered in 79 patients with virological-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
174
1
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(192 citation statements)
references
References 32 publications
(50 reference statements)
8
174
1
9
Order By: Relevance
“…In studies that analyzed treatment with lamivudine in HBeAgnegative patients or those with advanced liver fibrosis, sustained viral suppression was associated with the decrease in complications of cirrhosis and hepatocellular carcinoma. 11,19,20 A recent meta-analysis showed that the risk of hepatocellular carcinoma can be significantly decreased with viral suppression through antiviral therapy. 21 After NA withdrawal, relapse of viral infection can occur in most HBeAg-positive individuals that did not loose the HBeAg, as well as in HBeAg-negative individuals.…”
Section: Viral Suppression Of Hbv-dnamentioning
confidence: 99%
“…In studies that analyzed treatment with lamivudine in HBeAgnegative patients or those with advanced liver fibrosis, sustained viral suppression was associated with the decrease in complications of cirrhosis and hepatocellular carcinoma. 11,19,20 A recent meta-analysis showed that the risk of hepatocellular carcinoma can be significantly decreased with viral suppression through antiviral therapy. 21 After NA withdrawal, relapse of viral infection can occur in most HBeAg-positive individuals that did not loose the HBeAg, as well as in HBeAg-negative individuals.…”
Section: Viral Suppression Of Hbv-dnamentioning
confidence: 99%
“…These patients remained in remission after 5 years during a median follow-up period of 36 months, and virologic breakthrough associated with resistance was reported to be 33% in a median period of 15 months (17). George et al (23) reported HBV DNA suppression rates in 209 patients with HBeAgnegative chronic hepatitis B as 73.2% at the end of the first year, 52.3% at the end of 2 years, 40% at the end of 3 years, and 34% at the end of 4 years, whereas failure rates were approximately 46% within this period. In another study, Vito et al reported HBV DNA suppression rates that were 88.6% in the first year, 63% in the second year, 48% in the third year, and 39% in the fourth year in 616 patients with HBeAg negative chronic hepatitis B; the virologic failure rate was 33% under lamivudine (13).…”
Section: Discussionmentioning
confidence: 97%
“…Cet analogue nucléosidique dont la tolérance est excellente a permis d'induire une réponse chez la majorité des malades [10,11]. Néanmoins, son utilisation a été rapidement limitée par l'émergence de mutations de résistance responsables d'une perte d'efficacité et d'une réactivation virale particulièrement sévère chez les malades atteints de cirrhose [11]. La fréquence de ces résistances augmentait de 20 % à la première année pour atteindre 70 % à la cinquième année de traitement [11].…”
Section: Quel Traitement Antiviral ?unclassified
“…Néanmoins, son utilisation a été rapidement limitée par l'émergence de mutations de résistance responsables d'une perte d'efficacité et d'une réactivation virale particulièrement sévère chez les malades atteints de cirrhose [11]. La fréquence de ces résistances augmentait de 20 % à la première année pour atteindre 70 % à la cinquième année de traitement [11]. Des études à long terme chez des malades à fibrose sévère ont montré que le traitement diminuait de façon significative par rapport à un placebo le risque d'évolution vers la cirrhose, la survenue de complications et de l'hépato-carcinome [12].…”
Section: Quel Traitement Antiviral ?unclassified